Non Descent Vaginal Hysterectomy: A Rational Surgical Approach - Zahan, Arifa Akter; Shahnewaz, Kh; Salma, Ummay (KYAMC Journal, 2017)
Aims: To evaluate the rational approach of non-descent vaginal hysterectomy in advancing gynaecology practice. Study Design: Retrospective study and period from 1st July 2013 to 31st June 2014. Setting Kumudini Women's Medical College & Hospital, Mirzapur, Tangail. Patients: All selective patients requiring hysterectomy for benign gynecological disorders who did not have any uterine prolapse were recruited for this study. In bigger size uterus morcellation techniques like bisection, debulking, myomectomy, slicing, or combination of these were used to remove the uterus. Main outcome measures: Data regarding indication, age, parity, uterine size, estimated blood loss, length of operation, complication and hospital stay were recorded. Results: A total of 50 cases were selected for non-descent vaginal hysterectomy all of them successfully underwent non-descent vaginal hysterectomy. Commonest age group was (41-45 years) i.e. 46%. All patients were parous. Uterus size was less then 8 wks 21 cases, 8wks to 12 wks in 27 cases, more then 12 wks 02 cases. Commonest indication was DUB of uterus (44%). Mean duration of surgery was 50.5 minutes. Mean blood loss was 100ml. Blood transfusion was required in four cases. Average duration of hospital stay was 3.1 days. Complications were minimal which included UTI and Vault infection. Conclusions: NDVH is safe feasible and patient friendly. We suggest that our modern gynecologist will be more expertise and familiar to this procedure in near future. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 637-641